Poland: employment relations and the crisis... of its neighbours - Meardi, Guglielmo; Trappmann, Vera (Bratislava, 2013)
"This article describes the evolution of social dialogue and collective bargaining in Poland between 2008 and 2012, arguing that the effects of the crisis have been asymmetrical in two ways. First, while Poland is the only EU country to have avoided recession in macroeconomic terms, the crisis has actually disproportionately affected labour through higher unemployment and worsening employment conditions. Secondly, in a decentralized system like the Polish one, effects of the crisis have differed by sector. Sectors exposed to international competition such as the automotive and steel sectors have suffered from job losses and major restructuring, while services and construction have withstood better. While social dialogue has been temporarily re-legitimized during the crisis, it plays only a sporadic role and a flexible, unsecure employment system remains in place."